SELF-CONCEPT AND ITS RELATIONSHIP TO CREATIVE THINKING AMONG FOOTBALL PLAYERS - Dr. Haidar Abdulwahid Ghadhban (Scholars Digest Publishing, 2025)
This research aims to study the concept of self and its relationship to creative thinking among football players, as the concept of self is one of the basic psychological factors that affect the level of players' performance and decision-making during matches. Creative thinking also represents the player's ability to find unconventional solutions and adapt to the variables of the game. The research relies on scientific methods to measure the relationship between these two variables, which contributes to improving the understanding of coaches and psychological researchers of the mechanism of developing sports performance by enhancing players' self-confidence and stimulating their creative abilities.
Keywords: Performance, abilities, relationship, technical physics, football players.